Extinction - Rayson, Hannie, 1957- (Currency Press Pty Ltd., 2017)
Extinction delves deep into the heart of our own morals, choices and tightly held convictions. It wraps an important conservation message around a unique and personal human story. A wild, rainy night, a twist of fate and an injured tiger quoll bring together a passionate environmentalist and an unlikely Good Samaritan. Both are hell-bent on saving the species, but intentions are murky. What will be compromised in the quest to save the quoll? Nothing is black and white in this intriguing story about love, sex, money and power.